Hubungan Tingkat Pengetahuan Tentang Antibiotik dengan Sikap dan Tindakan Penggunaan Antibiotik Tanpa Resep pada Mahasiswa/i Universitas HKBP Nommensen Medan - Mega Oktavia Sianturi; Henny Erina Saurmauli Ompusunggu; Djohan . . (Universitas Baiturrahmah, 2021)
Introduction: Antibiotics are drugs that are used to prevent and treat infections caused by bacteria. Inappropriate use of antibiotics can cause various problems, such as bacterial resistance to antibiotics. One of the causes of bacterial resistance to antibiotics is the irrational in non prescription use of antibiotics. Aims: to determine the association of knowledge level about antibiotics with attitude and action level in non prescription use of antibiotics in Universitas HKBP Nommensen students. Method: There was 210 active students of Universitas HKBP Nommensen were included as respondents in this cross sectional study. The level of knowledge, attitudes and actions of respondents were measured using a questionnaire. Chi Square test was used to analyzed the association of knowledge with attitude and action of respondents. Result: There was no significant association of knowledge level about antibiotics with attitude and action level in non prescription use of antibiotics in Universitas HKBP Nommensen students (p > 0,005). Conclusion: Knowledge is not a dominant factor influencing both attitude and action in non prescription use of antibiotics.